Use of heart rate variability in the training of elite wrestlers - Korobeynikov, G.; Korobeinikova, L.; Raab, M.; Kokhanevich, A.; Korobeinikova, I. (International Journal of Wrestling Science, 2023)
One of the methods of training support for elite wrestlers is the assessment of the objective state of the body. Training and competition are interconnected by psycho-emotional factors that can affect the effectiveness of sports activities (Périard et al, 2015; Pryimakov et al, 2016). Considering that psychophysiological functions constitute the most important link in the formation of psychoemotional response in situations of extreme states, it is logical to expect a connection between stress resistance and indicators of perception and information in elite wrestlers (Radchenko 2012; Korobeynikov et al, 2021). As is known, the physiological reaction to the extreme conditions of the competition is characterized by the psychoemotional stress of athletes (Chernozub et al., 2019). A number of works indicate that stress resistance affects the ability to endure training loads and the ability to train elite athletes (Freitas et al, 2013). The cause of stress is a multifactorial stimuli that affects the decrease in the performance of athletes (Gustafsson et al, 2017). The leading cause the decline in performance is the imbalance between stress and recovery after training (Hartmann et al, 2000). One of the main links in the stress response during emotional stress is the autonomic nervous system (Laborde et al, 2018). In previous studies, the results of the relationship of adaptive response to intense physical and emotional stress were obtained (Korobeinikov et al., 2021). The mechanism of stress resistance and coping in the psychoemotional state of competitive activity has been studied (Barbas et al., 2011). Traditionally, one of the indicators of stress in the psycho-emotional state is heart rate variability. In response to a competitive stressful situation, a functional system is formed that provides muscular activity in highly qualified wrestlers (Theophilos et al., 2011). Modern Olympic wrestling is spectacular with a high intensity of competitive fight. This is a situation related to changes in United World Wrestling competition rules over the past ten years (Dokmanac et al., 2018). In this regard, the need to revise the systemic preparedness of elite wrestlers is very urgent. In addition, an increase in the intensity of competitive activity leads to a tension in the physiological regulation of the body in athletes (Kerimov et al., 2019). Therefore, studying the physiological mechanisms of the stress response of heart rate variability in competitions among elite wrestlers is of great importance. In addition, the development of a method of objectively monitoring the actual condition of elite wrestlers is a key direction in optimizing the training process. Therefore, the study of the stress response mechanisms of heart rate variability is of great importance for the training of elite wrestlers.